Management of financial institutions: notes and cases - Robichek, Alexander A.; Coleman, Alan B.; Stanford University (United state of America Holt, Rinehart and Winston, 1967)
This book emphasizes on the application of analytical techniques to the solution of significant financial problems.
"The material in this book is ... used in the Management of Financial Institutions course at the Stanford Graduate School of Business."
mf 22/01/2019
Loans
Keywords: Financial institutions